Promising selective MAO-B inhibition by sesamin, a lignan from Zanthoxylum flavum stems - Shaymaa M. Mohamed; Narayan D. Chaurasiya; Nesma M. Mohamed; Soad A.L. Bayoumi; Babu L. Tekwani; Samir A. Ross (Elsevier, 2020)
Monoamine oxidase inhibition is an important therapeutic approach for various neurodegenerative disorders. Reversible MAO inhibitors selectively targeting only one isoform possess substantial merit in terms of safety, efficacy, and side effect profile. This study aimed to isolate the secondary metabolites of Zanthoxylum flavum stems and evaluate their recombinant human MAO inhibition, antimicrobial, and antiprotozoal activities. As a result, fourteen compounds were isolated and identified (nine of them were reported from Z. flavum for the first time). Compound 3 (sesamin) exhibited potent selective MAO-B inhibition (IC50 value of 1.45 ± 0.05 µM) which reported herein for the first time. Compound 2 showed selective MAO-A inhibition activity, compound 5 exhibited good trypanocidal activity, and compound 7 displayed moderate antibacterial activity. The promising MAO-B inhibitory activity of sesamin provoked us to further explore the kinetic properties, the binding mode, and the underlying mechanism of MAO-B inhibition by this lignan. This detailed investigation substantiated a reversible binding and mixed MAO-B catalytic function inhibition via sesamin (Ki: 0.473 ± 0.076 μM). Selectivity and reversibility of sesamin on MAO-B provide exciting prerequisites for further in vivo investigation to confirm its therapeutic potentiality. Keywords: Zanthoxylum flavum, Rutaceae, Sesamin, Monoamine oxidase inhibition, Antimicrobial, Antiprotozoal